BELT CONVEYOR DESIGN FOR PRINTING BARCODE SCANNER MECHANISM - Ghany Heryana; Adang Saepudin; Andi Ciswanto (Jurnal Teknologika, 2020)
Belt conveyor is an intensive material transfer machine used in every branch of industry such as the casting industry, paper industry, food industry, coal mining industry and, so on. Most industries use the belt conveyor itself because belt conveyors can operate efficiently, practically, also economically. Transported materials can be bulk load or unit load, as well as easy maintenance and operation. Therefore it is necessary to design a conveyor belt according to the type of material to be transported. The design carried out is the design or engineering of conveyor belts, calculation of conveyor belt capacity, calculation of motor power, machine element analysis, and frame material used. The results obtained include making a belt conveyor unit, load design, designing a belt conveyor unit load with a carrying capacity (Qt) 5.2 ton per hour, loading weight - belt conveyor length (Wm) 8.66 kg/m, belt load maximum (Fmax) 165.65 kg, motor power 0.5 HP. The belt used standard type PVC food heat resistance up to 90°C. The frame belt conveyor uses SS 304 standard food material.